2018
DOI: 10.1186/s13027-018-0211-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human papillomavirus among Wenzhou women diagnosed with cervical intraepithelial neoplasia and cervical cancer

Abstract: BackgroundHuman papillomavirus (HPV) is associated with an increased risk of cervical cancer. Using a vaccine to prevent HPV infections could be a cost-effective strategy to decrease the incidence of cervical cancer. Learning about the characteristics of CIN patients with HPV infection in Wenzhou is a key step in guiding the use of HPV vaccines and screening for cervical cancer.MethodsWe undertook a retrospective analysis including 2612 women who were treated in the Department of Gynecology and Obstetrics from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 32 publications
2
19
1
Order By: Relevance
“…This genotype was also the most persistent in all cancerous and precancerous conditions. The prevalence of HPV 16 over the other genotypes (among these studies) is in agreement with previous reports from different geographical areas [20,21,22]. Few studies have been conducted in Africa to assess the distribution of HPV genotypes (HPV 58 was common in the current studies).…”
Section: Discussionsupporting
confidence: 91%
“…This genotype was also the most persistent in all cancerous and precancerous conditions. The prevalence of HPV 16 over the other genotypes (among these studies) is in agreement with previous reports from different geographical areas [20,21,22]. Few studies have been conducted in Africa to assess the distribution of HPV genotypes (HPV 58 was common in the current studies).…”
Section: Discussionsupporting
confidence: 91%
“…HPV DNA testing using the HPV Nucleic Acid Test Kit (Tellgen, Shanghai, China) via PCR technology was conducted to identify 27 genotypes in the Luminex 200 system 12. The HPV DNA chip was not only capable of detecting various HPV subtypes simultaneously but also showed higher sensitivity and specificity than those of traditional cytology.…”
Section: Methodsmentioning
confidence: 99%
“…In 2018, clinical, epidemiological, and clinicopathological studies reported HPV58 to be the second or third most predominant genotype in precancerous CIN I, II, III, and ICC lesions, a higher grade of squamous intraepithelial or cell carcinoma, and adenocarcinoma of HPV positive patients in different geographical regions of China [11]. Seven provinces of China have reported hrHPV-mediated cervical cancer incidences, namely, Guangdong, Liaocheng, Shanghai, Wenzhou, Wuhan, Southwestern China, and Western China [13,14,15,16,17,18,19]. Zhang et al [20] reported that the HPV16 (6.4%) and HPV58 (5.3%) genotypes were predominantly found in males who had recently been involved in sex, in Shanghai.…”
Section: Introductionmentioning
confidence: 99%